NEO-COLONIAL INFLUENCES ON AFRICAN DEMOCRACY: ASSESSING THE IMPACT OF EXTERNAL POWERS ON GOVERNANCE AND SOVEREIGNTY IN THE 21ST CENTURY - QUEEN OLUBUKOLA AYENI; YAOUBA OUSMANOU (International Studies Journal, 2025)
Africa’s democratic evolution in the 21st century remains profoundly influenced by external actors, raising concerns about neocolonial interventions in governance and sovereignty. For decades, African nations have struggled with the legacies of colonial rule, which continue to manifest through economic dependencies, political interference, and conditional aid from former colonial powers and global institutions. The rationale for this study stems from the increasing debate over the extent to which these external influences undermine genuine democratic consolidation and self-determination in African states. While extensive research exists on colonial legacies, there is a gap in contemporary analysis of how neocolonial practices shape political institutions, electoral processes, and policy decisions in modern Africa. This study aims to assess the mechanisms through which foreign powers exert control over African democracies, the implications for state sovereignty, and potential pathways for reinforcing independent governance structures. A qualitative research approach is employed, utilizing case studies of selected African countries and policy analysis. Key findings suggest that financial aid, diplomatic pressures, and military interventions serve as tools of neocolonial dominance, often prioritizing external interests over national development. The study concludes that strengthening regional cooperation, economic self-sufficiency, and institutional reforms are crucial to mitigating external influences and fostering authentic democratic governance in Africa.